Experimental Study on Mechanical Properties of Cemented Paste Backfill under Temperature-Chemical Coupling Conditions - Yin Liu; Hao Li; Haifeng Wu (Advances in Materials Science and Engineering)
To investigate the effect of temperature-chemical coupling on the mechanical properties of cemented paste backfill, three temperatures (20°C, 35°C, and 50°C) and sodium sulfate solution mass concentrations (3%, 5%, and 7%) are applied to simulate the complex environment in a mine. Uniaxial compressive strength and the CPB stress-strain relationship are investigated by applying stress, and the deterioration mechanism was analyzed theoretically according to physical and chemical reactions. At the same time, a structural model of the CPB deterioration mechanism under TC coupling is constructed. Combined with analysis through X-ray diffraction and scanning electron microscopy, it is shown that ettringite and gypsum are the main erosive substances that destroy the structure of CPB and that increased temperatures accelerate the chemical reaction. The concentration change consumes calcium hydroxide, changing the relationship between ettringite and gypsum. Sodium sulphate crystallization is the main form of physical deterioration. The continuous load accelerates the inelastic deformation time of CPB, resulting in a large yield deformation process.